Eating disorders across population groups with different weight status in Belgium: evidence for an integrative preventative approach - Fara Geerinck; Sabine Drieskens; Lydia Gisle; Stefanie Vandevijvere; Rana Charafeddine (BMC Public Health)
Abstract Background It is a common misperception that eating disorders (ED) predominantly affect individuals with underweight. This study aims to clarify the prevalence and odds of living with an ED across different weight groups within the Belgian population, and to identify sociodemographic factors associated with the comorbidity of ED and overweight or obesity. Methods Data for this study was sourced from the 2018 Belgian Health Interview Survey (BHIS). This is a cross-sectional survey that collects health information from approximately 10,000 individuals living in Belgium through face-to-face interviews and self-administered questionnaires. Data collection involved questions on EDs (SCOFF questionnaire), height and weight, and sociodemographic characteristics. The prevalence of EDs was determined through descriptive statistics. Multivariable logistic regression models were employed to assess the odds of living with an ED across different weight categories and to identify sociodemographic variables (age, sex, education, income, and ethnicity) linked to the comorbidity of EDs and obesity/overweight. Results General ED prevalence in this study was 7.1%. The prevalence of EDs was highest among individuals with obesity (12.3%, 95% CI: 10.0–15.1%) compared to those with normal weight (5.5%, 95% CI: 4.4–6.9%). Individuals with obesity had three times higher odds of living with an ED (adjusted odds ratio (AOR): 3.0, 95% CI: 2.1–4.1). Individuals with overweight also had increased odds of living with an ED (AOR: 1.4, CI: 1.0–2.0). The comorbidity of EDs and obesity/overweight was significantly linked to low educational levels (AOR: 1.8, 95% CI 1.1–2.8), financial difficulties (AOR: 1.9, 95% CI 1.4–2.7), and maternal non-EU origin (AOR: 2.4, 95% CI 1.6–3.7). Conclusions EDs disproportionally affect people with higher weight. This underscores the necessity for public health interventions that address the intertwined nature of EDs and obesity. Traditional weight-centric health campaigns focusing on individual responsibility may inadvertently contribute to the problem by promoting weight stigma. An integrative preventative approach holds promise for more effective management and prevention of EDs and obesity in the Belgian population.